EXPANSÃO E INTERIORIZAÇÃO DAS UNIVERSIDADES FEDERAIS: UMA ANÁLISE DO PROCESSO DE IMPLEMENTAÇÃO DO CAMPUS DO LITORAL NORTE DA UNIVERSIDADE FEDERAL DA PARAÍBA - Francivaldo dos Santos Nascimento (Universidade Federal de Santa Catarina, 2015)
The Brazilian federal government, since 2004, has been concerned with expand into theinterior the federal public universities. In this context, from 2005, the UFPB recovered itsinternalization process, by the creation of the Campus IV (North Coast), located in the citiesof Rio Tinto and Mamanguape. This article analyzes the implementation process of theCampus of the North Coast of UFPB. The theoretical foundation addressed the public policycycle, in particular the implementation stage, highlighting the model of Smith (1973), andpublic policies of higher education in the FHC and Lula. The research was descriptive andqualitative, conducted through a case study. The primary data were collected throughinterviews with nine people, professors and technical administrators, who participated directlyin the implementation process. Were also used secondary data, such as institutionaldocuments, and newspaper articles published in the local press. The data analysis was thecontent analysis. The data allowed the analysis of the implementation process in theinstitutional perspective, the political and institutional aspects; in materials perspective, thetechnical and administrative aspects; and procedural perspective, relations with society. Thesurvey results revealed that the implementation process had a political influence, especially inthe choice of cities that receive the campus. The implementation of the Campus IV was astrategic action with an enormous educational, social and economic relevance, carried out,however, from some mistakes, as lack of proper planning and difficulties in the execution ofinfrastructure projects.